INFLUENCE OF WORKLOAD AND ADAPTABILITY ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION PT. INDONESIAN SHARIA BANK ARE LHOKSEUMAWE - Harris Fakhrial; Herman Fithra; Marbawi (RADJA PUBLIKA, 2024)
This research aims to determine the effect of workload and adaptability on employee performance through job satisfaction at PT. Indonesian Sharia Bank Lhokseumawe Area. The data in this research used primary data in the form of a questionnaire which was prepared according to the research variable measurement indicators and distributed to 168 employees of PT. Bank Syariah Indonesia Lhokseumawe Area with a sampling technique carried out in the first stage, stratified random sampling, then carried out using a simple random sampling technique on the respondents in this study, employees of PT. Indonesian Sharia Bank Lhokseumawe Area. The data analysis method used is structural analysis (SEM) and processed with the moment of structural analysis (Amos) program, namely a multivariate analysis technique which is a combination of factor analysis and regression analysis which aims to test the relationship between variables in a model , both that are between indicators and constructs, or relationships between constructs. The research results found that there was an influence of workload and adaptability on job satisfaction and workload and adaptability also had an influence on employee performance, then there was an influence of job satisfaction on employee performance. Furthermore, the results of this research show that job satisfaction moderates the influence of workload and adaptability on employee performance.